2022
DOI: 10.1007/s10508-022-02505-2
|View full text |Cite
|
Sign up to set email alerts
|

Masturbation Prevalence, Frequency, Reasons, and Associations with Partnered Sex in the Midst of the COVID-19 Pandemic: Findings from a U.S. Nationally Representative Survey

Abstract: Despite well-documented individual, relational, and health benefits, masturbation has been stigmatized and is understudied compared to partnered sex. In a US nationally representative survey of adults, we aimed to: (1) assess the prevalence and frequency of participants’ prior-year masturbation, (2) describe reasons people give for not masturbating, (3) describe reasons people give for masturbating, and (4) examine the association between masturbation frequency and actual/desired partnered sex frequency in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…In a study conducted in a sample of 2068 women from the USA and Hungary, with a mean age of 28.8 (SD = 9.9; range 18-95), 94% reported masturbating in the last 12-24 months, with a medium of once per week or every two weeks [18]. These findings are partially supported by another recent study with 3878 participants from the U.S. with a mean age of 48.1 years (SD = 18.3, range 18-93) [17] that showed that significantly more men (60%) reported masturbating in the past month when compared to women (36.5%). Both men and women reported a patterned reason for solitary sex: to alleviate sexual tension [19,20].…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…In a study conducted in a sample of 2068 women from the USA and Hungary, with a mean age of 28.8 (SD = 9.9; range 18-95), 94% reported masturbating in the last 12-24 months, with a medium of once per week or every two weeks [18]. These findings are partially supported by another recent study with 3878 participants from the U.S. with a mean age of 48.1 years (SD = 18.3, range 18-93) [17] that showed that significantly more men (60%) reported masturbating in the past month when compared to women (36.5%). Both men and women reported a patterned reason for solitary sex: to alleviate sexual tension [19,20].…”
Section: Introductionsupporting
confidence: 52%
“…Historically, engaging in solitary sexual experiences, commonly designated as "masturbation", has been associated with negative connotations, immoral behavior, and illness [16]. Nowadays, it is widely recognized as a common and beneficial sexual practice [17]. In a study conducted in a sample of 2068 women from the USA and Hungary, with a mean age of 28.8 (SD = 9.9; range 18-95), 94% reported masturbating in the last 12-24 months, with a medium of once per week or every two weeks [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The act is usually accompanied by sexual fantasies or erotic literature, pictures, or videos and may also include the use of mechanical devices (e.g., a vibrator) or self-stimulation of other body parts, such as the anus or nipples. Masturbation is a common sexual behavior with, for example, 60% of men and 36.5% of women engaging in it over the preceding month in a US sample (Herbenick et al, 2023). The corresponding figures in a UK 16-44-year-old sample were 73% and 37% (Gerressu et al, 2008).…”
Section: Masturbationmentioning
confidence: 99%
“…In fact, one sexual behavior that may help with pleasure inequalities is masturbation (solo and mutual) as orgasm rates and orgasm satisfaction do not differ between men and women, and between women in same-sex and women in mixed-sex relationships during self-stimulation (Blair et al., 2018 ; Wetzel & Sanchez, 2022 ). Also, although people report various reasons to masturbate, the primary cited motivation is pleasure (Carvalheira & Leal, 2013 ; Herbenick et al., 2023 ; Rowland, Kolba, et al., 2020 ). As sexual pleasure is linked with diverse sexual experiences (Ford et al., 2021 ; Mitchell et al., 2021 ; Reis et al., 2021 ), understanding the joyful aspects of types of masturbation (solo and mutual) in relationships is important.…”
Section: Introductionmentioning
confidence: 99%